Spatio-temporal genetic patterns in Mediterranean bluefin tuna : population structuring and retention of genetic diversity - Riccioni, Giulia (2010)
We assessed spatio-temporal genetic patterns in Mediterranean samples of bluefin tuna (BFT) to look for signs of population structuring and genetic erosion, which might be related to stock overexploitation and depletion. We analyzed microsatellite variation at seven neutral loci on seven contemporary bluefin tuna samples collected from the Alboran Sea to the Levant Sea (N=316) and in two historical samples (N=99) collected from 1911 to 1926 in the southern Tyrrhenian and Adriatic Seas. We found signs of widespread and deep spatial genetic structuring in both contemporary (mean FST =0.014, P < 0.0001) and historical bluefin tunas (FST=0.020, P < 0.0001). These findings coherently confirm previous data obtained on a limited number of samples and reinforce the possibility that the Mediterranean is inhabited by reproductively isolated sub-populations. Temporal genetic analyses did not find evidence of genetic bottlenecks in Mediterranean bluefin tuna samples. However, since samples displayed heterogeneity of population demographic parameters, Mediterranean bluefin tuna subpopulations might have partially independent dynamics. Our results illustrate that in Mediterranean, structured bluefin tuna populations retain a high level of genetic diversity across space and time, despite possible demographic declines and population changes.